Characterization of prophage-like elements in plant pathogenic Xanthomonas species - Ferreira, Nataly Figueiredo (2022)
Bacteriophages are viruses that infect prokaryotes that are present in diverse environments. Prophages are bacteriophages with genome into the host genome and have been considered part of bacteria mobilome. For instance, bacteriophages may encode proteins that increase bacteria toxicity and virulence, confer genetic variability, and facilitate horizontal gene transfer, improving bacterial fitness. The Xanthomonas genus harbors many phytopathogenic bacteria that impair many crops worldwide. However, there is a scarcity of studies that describes bacteriophage distribution and diversity within this genus. Given this, our study aims to identify and characterize the presence of prophage-like elements in three species belonging to the Xanthomonas genus: X. axonopodis, X. campestris and X. citri. We found prophage-like sequences in 98% of the analyzed genomes, whereby more than one prophage-like was detected within the same bacterial genome, event denominated as polilysogen. The prophages-like from Xanthomonas spp. belonged to four viral families (Myoviridae, Siphoviridae, Podoviridae, Inoviridae), three families belonging to the Caudovirales order and one belonging to the Tubulavirales order (Inoviridae). Furthermore, many prophages-like harbored genes of putative bacterial origin, indicating horizontal gene transfer between the virus and host, such as genes encoding virulence factors. Taken together, these results indicated that prophages-like are widespread in Xanthomonas spp., influencing the genome diversity and fitness of these bacteria. Keywords: Bacteriophage. PHASTER. Genome plasticity. Bacteria fitness.